The role of parasitic Hymenoptera in biological control of forest insect pests in South Korea: A review of invasive and native species management - Jongok Lim (Biological Control)
Forests are vital ecosystems that provide considerable environmental, social, and economic benefits. However, they are increasingly threatened by both invasive and native insect pests. This review examines the role of parasitic Hymenoptera species in managing key forest pests in South Korea, including invasive species such as Metcalfa pruinosa (Say) (Hemiptera: Flatidae), Lycorma delicatula (White) (Hemiptera: Fulgoridae), Hyphantria cunea (Drury) (Lepidoptera: Erebidae), and Thecodiplosis japonensis Uchida and Inouye (Diptera, Cecidomyiidae), as well as native pests like Monochamus alternatus Hope, M. saltuarius (Gebler) (Coleoptera: Cerambycidae), and Lymantria dispar asiatica (Butler) (Lepidoptera: Erebidae). Biological control strategies, particularly those utilizing natural enemies such as parasitoid species, have become increasingly prominent and environmentally sustainable alternatives to chemical methods. This review highlights recent advances in the mass rearing of parasitoids such as Sclerodermus harmandi Buysson (Hymenoptera: Bethylidae) and Neodryinus typhlocybae (Ashmead) (Hymenoptera: Dryinidae) and their effectiveness in reducing pest populations. Furthermore, this study provides a comprehensive review of the ecological and biological characteristics of these biological control agents, including their parasitism rates and roles in integrated pest management, to assess and introduce the current state of research on the natural enemies of key forest insect pests in South Korea. By synthesizing recent research, this paper underscores the importance of Hymenoptera-based biological control as a sustainable approach for promoting forest health and biodiversity conservation in South Korea.